Current‐Corrected Cycling Strategies for True Electrode Performance Measurement. Issue 2 (1st December 2021) - Yan, Zilai; Scott, Benjamin; Glazier, Stephen L.; Obrovac, Mark N.
Abstract: In battery research, galvanostatic cycling is the most widely used strategy to evaluate electrode performance. By applying pre‐set current throughout the test, this method often fails to accurately reflect electrode performance at the designed cycling rate (particularly for high‐rate cycling) because the actual capacity can be considerably affected by polarization and electrode degradation. To address this issue, a current‐corrected cycling method is proposed, in which the current is actively adjusted during cycling based on the measured capacity of previous cycles. Compared to the traditional method, which may result in cycling rates that are hundreds of times faster than the designed rate, the proposed cycling strategy can effectively measure rate‐dependent electrode performance precisely at designated rates. The authors believe this method is highly useful in electrode/battery performance evaluation for practical cell design, particularly in fast‐charging applications. Abstract : Towards true electrode performance measurement : The actual cycling rate [1/(lithiation time in hours)] of graphite electrodes cycled at different designed cycling rates using traditional galvanostatic cycling and current‐corrected galvanostatic cycling.